Application Of Cnc Simulator For CNC Machining Via CAD-CAM - Misman, Lailisa Nur (Universiti Sains Malaysia, 2017)
Most manufacturing industries use Computer Aided Design (CAD) and Computer Aided Manufacturing (CAM) transforms manufacturing system by improving productivity of production. The main purpose of Computer Numeric Control (CNC) Simulator is to create a faster production process and components and tooling with more precise amount of raw material thus minimizing waste, while simultaneously reduce energy consumption. This paper describes effective approaches of CNC simulators for CNC milling machine. Before real machining, several simulations are generated to identify excellent machining method. CAD/CAM software is most often used for machining of prototypes and finished parts. Machining parameters can affect the surface quality of product in CNC machining. The combination of synchronized movements on three axes restrict user machining a part with complex shape. The purpose of this research is to identify machining parameters for CNC Simulator and real machining. To compare machining simulations approached by using different CNC Simulators. Another purpose is to identify the accuracy of simulation and actual machining. CNC Keller, Mastercam X2 and CATIA V5 are used to identify the effective method to machining complex geometric shape in CNC machine; CNC 3- axis machine and CNC 5-axis machine. With different combinations of orientations sets, the total machining times were considered as the crucial of roughing and finishing. In the simulations studies, comparisons are made between those three CNC Simulators and real machining.